IMPLEMENTATION OF SCHOOL INFORMATION SYSTEM MANAGEMENT IN THE USE OF DIGITAL RESOURCES - Melan Nur Meilani (Educational Insights, 2023)
However, it requires management to manage this on a regular basis. In the current digital era, many schools have turned to information system management and integrated digital resources. On the other hand, although digital resources and information technology are growing, there are still shortcomings in their utilization. Many schools are limited in managing information systems, as well as limited in their understanding of technology. This study aims to explore the implementation of school information systems and digital resources. The research method used in the study was descriptive qualitative. Data collection techniques were conducted through interviews and observations. Data validity was tested using triangulation. The results showed that the implementation of information system management in the use of digital resources in one of the KCD VII schools in Bandung City has utilized the use of digital applications, namely ARKAS (School Activity and Budget Plan Application) and SIPD (Regional Development Information System). These applications facilitate planning, monitoring and help manage the use of resources, including budget allocations. The use of these applications improves efficiency, accuracy and transparency in school management. The role of teachers in using these digital applications is when entering grades. But in the context of teaching, the application of digital resources is still not running optimally. The information system in terms of communication between teachers, students, schools and parents shows inefficiency because there is no specific application that serves as a communication platform.